EFEKTIVITAS BIMBINGAN PRA NIKAH DAN PENGARUHNYA TERHADAP KESIAPAN CALON PENGANTIN DI KANTOR URUSAN AGAMA KECAMATAN BALOCCI KABUPATEN PANGKEP - Ahmad Muflihuddin Arjul Haq; Muhammad Fajri (Universitas Islam Negeri Alauddin Makassar, 2022)
This study discusses the Effectiveness of Premarital Guidance and its Effect on the Readiness of Brides-to-be in the Religious Affairs Office of Pangkep Regency District. The problem studied was how the effectiveness and influence of premarital guidance in the Religious Affairs Office of Balocci District, Pangkep Regency. This type of research is field research, which is a form of research that requires researchers to go directly to the field. The main source of this research is data in the field such as observations and interviews. The results of this study show that the implementation of premarital guidance in the Religious Affairs Office of Balocci District, Pangkep Regency as a whole has not been carried out effectively, so that the guidance providers need to improve the quality of marriage guidance, especially in terms of organizing materials and facilities and infrastructure. However, it is undeniable that the premarital guidance that has been carried out at the Religious Affairs Office of Balocci District, Pangkep Regency, has a positive influence on the readiness of the bride and groom, namely the increase in knowledge and the more mental maturity of the brides-to-be, so that they are better prepared to hold a wedding.